2018
DOI: 10.1038/s41598-018-23029-7
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors of Moraxella catarrhalis outer membrane vesicles are major targets for cross-reactive antibodies and have adapted during evolution

Abstract: Moraxella catarrhalis is a common human respiratory tract pathogen. Its virulence factors associated with whole bacteria or outer membrane vesicles (OMVs) aid infection, colonization and may induce specific antibodies. To investigate pathogen-host interactions, we applied integrated bioinformatic and immunoproteomic (2D-electrophoresis, immunoblotting, LC-MS/MS) approaches. We showed that OMV proteins engaged exclusively in complement evasion and colonization strategies, but not those involved in iron transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 81 publications
(96 reference statements)
1
34
0
Order By: Relevance
“…Hence, it is of interest to investigate the protective potency of OMVs in the light of their specificity to react with a target cell. In the present study, we used our well-characterized OMVs from Moraxella catarrhalis Mc6 [4,21] as model vesicles and characterized their protective potential against model membrane-active agents in various interspecies combinations. First, we examined the protective activity of OMVs in bacterial intra- and interspecies systems and mode of observed protection, showing by HPLC-UV, zeta potential measurement, and o-nitrophenyl-β-D-galactopyranoside ONPG-based permeabilization assay, highly effective sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is of interest to investigate the protective potency of OMVs in the light of their specificity to react with a target cell. In the present study, we used our well-characterized OMVs from Moraxella catarrhalis Mc6 [4,21] as model vesicles and characterized their protective potential against model membrane-active agents in various interspecies combinations. First, we examined the protective activity of OMVs in bacterial intra- and interspecies systems and mode of observed protection, showing by HPLC-UV, zeta potential measurement, and o-nitrophenyl-β-D-galactopyranoside ONPG-based permeabilization assay, highly effective sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since M. catarrhalis can induce apoptosis in primary alveolar epithelial cells and A549 cells through engagement of surface protein UspA1 to human CEACAM1 molecule [ 53 ], we can hypothesize that OMV-stimulated apoptosis could be at least in part mediated by this surface bacterial protein. Accordingly, as already mentioned, the presence of UspA1 in OMVs from Mc6 strain was confirmed by LC-MS/MS analysis [ 35 ]. Here, we have documented the expression of the CEACAM1 receptor on a certain fraction of A549 cells that also supports this hypothesis.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, M. catarrhalis diminishes A549 inflammation through engagement of the CEACAM1-binding motif using bacterial surface ubiquitous protein UspA1—which in turn abrogates the TLR2- and NF- κ B-triggered inflammatory response [ 46 ]. Having confirmed both the presence of UspA1 (ligand for CEACAM1) in OMVs from Mc6 strain [ 35 ] and CEACAM1 expression on a certain fraction of A549 cells (this study), our results regarding proinflammatory action of M. catarrhalis OMVs do not contradict the previous studies since, (i) studied here, OMVs were potent stimulants only in the presence of IL-1 β and (2) the diminished, but not abolished, proinflammatory response was documented both for UspA1-containing and UspA1-deficient OMVs [ 4 ]. Since changes in the CEACAM1 expression patterns of different fractions of A549 cells can alter their diverse functions [ 38 ], the confirmation of CEACAM1 expression is essential in studies on the interaction between M. catarrhalis and this line.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…M. catarrhalis produces large numbers of OMVs, and these nanoparticles carry most proteins also seen in the parent cell [94]. By using an integrated bioinformatic and immunoproteomic approach, the protein content in OMVs has been thoroughly analysed by Augustyniak et al [95]. Their study revealed that M. catarrhalis has adapted to the human host by a distinct path of evolution as compared to other Moraxella subspecies.…”
Section: The Terminal Pathway Binding Of Plasminogen and M Catarrhamentioning
confidence: 99%